The KASCADE-Grande observatory and the composition of very high-energy cosmic rays. (October 2015) - Arteaga-Velázquez, J C; Apel, W D; Bekk, K; Bertaina, M; Blümer, J; Bozdog, H; Brancus, I M; Cantoni, E; Chiavassa, A; Cossavella, F; Daumiller, K; de Souza, V; et al.
Abstract: KASCADE-Grande is an air-shower observatory devoted to the detection of cosmic rays with energies in the range of 10 16 to 10 18 eV. This energy region is of particular interest for the cosmic ray astrophysics, since it is the place where some models predict the existence of a transition from galactic to extragalactic origin of cosmic rays and the presence of a break in the flux of its heavy component. The detection of these features requires detailed and simultaneous measurements of the energy and composition of cosmic rays with sufficient statistics. These kinds of studies are possible for the first time in KASCADE-Grande due to the accurate measurements of several air-shower observables, i.e., the number of charged particles, electrons and muons in the shower, using the different detector systems of the observatory. In this contribution, a detailed look into the composition of 10 16 — 10 18 eV cosmic rays with KASCADE-Grande is presented.